Filozofie - vychova a vzdeiani J.A. Komensky a jeho vztaha zajem o dospeleho ćloveka - Pavlů, Jiři (Chowanna, 2005)
The essay is an attempt to connect the relationships between philosophy, upbringing, and education, which the author aims to compare while presenting the ideas of certain philosophers in the context of the history of philosophy. It also addresses issues related to the formation of a person through upbringing and education. The term "philosophy" comes from the Greek philo-sophia, meaning "love of wisdom." In a significant translation of the Greek original, philia refers to a feeling toward something, a focus on something. Philia represents love in the sense of affection, while sophia means wisdom. Philosophy as a discipline originates from ancient Greece in the 7th century BCE when thinkers began to explore the world freely, independently of mythology and religion, relying solely on human reason. According to Masaryk’s essential dictionary, philosophy is defined as a "kindness toward wisdom" and is primarily the result of systematic thinking about facts and expanding knowledge, for example, concerning the essence of matter, life, development, space, and truth. In the Concise Philosophical Dictionary, philosophy is described as "a science that seeks answers to the most fundamental problems concerning the world, knowledge, and individuals."